Pore size effects on physicochemical properties of Fe-Co/K-Al2O3 catalysts and their catalytic activity in CO2 hydrogenation to light olefins - Numpilai, T.; Chanlek, N.; Poo-Arporn, Y.; Wannapaiboon, S.; Cheng, C. K.; Siri-Nguan, N.; Sornchamni, T.; Kongkachuichay, P.; Chareonpanich, M.; Rupprechter, G.; Limtrakul, J.; Witoon, Thongthai (Elsevier, 2019)
In this work, the hydrogenation of CO2 to light olefins has been studied over the Fe-Co/K-Al2 O3 catalysts, while focusing on the impact by the pore sizes of Al2 O3 supports including 6.2 nm (S-Al2 3 ), 49.7 nm (M-Al2 O3 ) and 152.3 nm (L-Al2 O3 ) on the structure and catalytic performance. The characterization results demonstrate that the pore sizes of the Al2 O3 supports play a vital role on the crystallite size of Fe2 O3 , the reducibility of Fe2 O3 and the adsorption-desorption of CO2 and H2 . The catalyst with the smallest pore size (CS-Al2 O3 ) allows the formation of a small Fe2 O3 crystallite size due to pore confinement effects, yielding a low active component (Fe) after reduction at 400 °C for 5 h. The catalysts with the larger pore sizes of 49.7 nm (CM-Al2 O3 ) and 152.3 nm (CL-Al2 O3 ) provide the larger Fe2 O3 crystallite sizes which require a longer reduction time for enhancing degree of reduction, resulting in a high metallic Fe content, leading to a high CO2 conversion and a high selectivity toward hydrocarbon. Eliminating diffusion limitation by increasing the pore sizes of Al2 O3 supports can suppress the hydrogenation of olefins to paraffins and thus the largest pore catalyst (CL-Al2 O3 ) gives the highest olefins to paraffins ratio of 6.82. Nevertheless, the CL-Al2 O3 also favors the formation of C5+ hydrocarbon. Therefore, the highest light olefins yield (14.38%) is achieved over the catalyst with appropriated pore size (CM-Al2 O3 ).